A method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash

SiO2 aerogel composite fiber was extracted through fly ash, and a sol-gel method and mixed precursor method were used, combined with glass fiber reinforcement, to prepare composite insulation materials with high mechanical properties and low thermal conductivity, which solved the problems of large brittleness and poor flexibility of existing SiO2 aerogels, and achieved significant improvement in material performance and efficient utilization of resources.

CN116675467BActive Publication Date: 2025-04-29CHINA UNIV OF MINING & TECH +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310631257.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-31
Publication Date
2025-04-29
Estimated Expiration
2043-05-31

AI Technical Summary

Technical Problem

The existing SiO2 aerogels have high brittleness and poor flexibility, and cannot obtain strong bulk materials, which limits the application of SiO2 aerogels.

Method used

SiO2 aerogel composite fiber was extracted through fly ash, SiO2 aerogel was prepared by sol-gel method, and Si-O-Si chains were extended by the mixed precursor method to form a flexible silicon-based aerogel with high resilience properties. Combined with glass fiber reinforcement, a composite insulation material with high skeleton strength was prepared.

Benefits of technology

It significantly improves the mechanical properties and socio-economic utilization value of composite insulation materials, while reducing the production cost of SiO2 aerogels and broadening the application field of fly ash.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the field of resource recovery technology, and specifically discloses a method for extracting SiO2 aerogel composite fibers from fly ash to prepare thermal insulation materials, the method comprising heating and drying fly ash, grinding and calcining fly ash and sodium carbonate, acid leaching of calcined powder to enrich silicon slag, alkali leaching of silicon slag to extract sodium silicate, ion exchange of sodium silicate supernatant and gel preparation of SiO2 aerogel, and also comprising fiber pretreatment and fiber and SiO2 aerogel mixing and curing process. The present invention adopts a sol-gel method to prepare SiO2 aerogel, adopts a one-step method to complete solvent exchange and surface modification, and reduces the production cost of SiO2 aerogel; adopts a normal pressure drying method to mix and solidify glass fiber and SiO2 aerogel to prepare a composite thermal insulation material, uses high temperature resistant material glass fiber as a reinforcing phase, improves the skeleton strength of the composite thermal insulation material, and thus significantly improves the mechanical properties of the composite thermal insulation material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of resource recovery, and in particular to a method for preparing a thermal insulation material by extracting SiO2 aerogel composite fibers from fly ash. Background Art

[0002] Fly ash is a powdery substance or discharge from the bottom of the furnace chamber collected by the dust collecting device from the flue after the coal powder is burned in the boiler. At present, the comprehensive utilization of fly ash is mainly concentrated in the fields of roadbed backfill, cement, concrete and other material preparation. The way of using fly ash is relatively rough. Although it can greatly solve the problem of fly ash accumulation, the utilization value is low. The valuable elements in fly ash have not been effectively extracted, and no greater social and economic utilization value has been achieved. Since fly ash is rich in silicon sources, it can be used as a precursor of SiO2 aerogel after further processing. Since fly ash is cheap and the fly ash production capacity is huge and can maintain a stable supply, the use of fly ash to prepare SiO2 aerogel can not only reduce the production cost of SiO2 aerogel, but also broaden the application field of fly ash and improve the social and economic utilization value of fly ash. However, conventional SiO2 aerogel is brittle and has poor flexibility. It usually exists in powdered aerogel, and it is impossible to obtain a strong block material, which limits the application of SiO2 aerogel. Summary of the invention

[0003] Purpose of the invention: The purpose of the present invention is to provide a method for extracting SiO2 aerogel composite fibers from fly ash to prepare thermal insulation materials, so as to realize the resource utilization of fly ash and improve the performance of SiO2 aerogel composite thermal insulation materials.

[0004] Technical solution: The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash of the present invention comprises the following steps:

[0005] Step 1: placing the fly ash in a constant temperature drying oven for heating and drying to obtain dry fly ash;

[0006] Step 2: Mix and grind the dry fly ash and sodium carbonate in a mass ratio of 1:0.5-1:1, place in a muffle furnace for calcination, calcine at a calcination temperature of 750-900 °C for 2-4 h, and fully grind the calcined material to obtain a calcined powder;

[0007] Step 3: adding the calcined powder to a sulfuric acid solution with a concentration of 10-30 wt.% according to a solid-liquid ratio of 0.5:1-1:1, placing it in a magnetic heating stirrer, stirring it at an acid leaching temperature of 80-90°C for 40-60 min, filtering it, washing it to neutrality, and obtaining silicon slag;

[0008] Step 4: adding silicon slag to a NaOH solution with a concentration of 10-15 wt.% according to a solid-liquid ratio of 0.5:1-1:1, placing the mixture in a reactor, reacting the mixture at a reaction temperature of 150-200 °C for 90-120 min, adding the solid-liquid slurry to a centrifuge for liquid-solid separation, and separating to obtain a sodium silicate supernatant;

[0009] Step 5: dilute and hydrolyze the sodium silicate supernatant according to a silicon-water volume ratio of 1:2 to 1:5, pass the diluted and hydrolyzed sodium silicate supernatant through an ethylene-type cation exchange column for ion exchange, and then drop ammonia water to adjust the solution pH to 5.0 to 6.0;

[0010] Step 6: Add the pH-adjusted solution into an electromagnetic heating stirrer, heat and stir evenly, and then let it stand to gel to obtain a hydrogel;

[0011] Step 7: Add ethanol to the hydrogel, then add n-heptane solvent and surface modifier in a 1:1 volume ratio, place in a water bath, and bathe at a water bath temperature of 30-50 °C for 8-12 h to obtain SiO2 aerogel;

[0012] Step 8: Immerse the glass fiber in 95% pure anhydrous ethanol, perform ultrasonic cleaning in an ultrasonic cleaning machine to remove oil stains and residual impurities in the fiber, wash the cleaned fiber and then soak it in an antistatic agent;

[0013] Step 9: Dissolve SiO2 aerogel and hot melt adhesive powder in n-heptane solvent at a mass ratio of 4:1, immerse the antistatic treated fiber in n-heptane solvent at a mass ratio of fiber to SiO2 aerogel of 1:9-3:7, mix thoroughly, and then put into an oven for curing; after cooling, obtain a glass fiber reinforced SiO2 aerogel composite thermal insulation material.

[0014] Preferably, in step 1, the drying temperature is 150-180° C. and the drying time is 24-30 h.

[0015] Preferably, the particle size of the calcined powder after grinding in step 2 is 50-100 μm.

[0016] Preferably, the concentration of aqueous ammonia in step 5 is 60-70 wt.%.

[0017] Preferably, in step 6, the gel temperature is 40-50° C. and the gel time is 24-36 h.

[0018] Preferably, the surface modifier in step 7 is a mixture of trimethylchlorosilane and hexamethyldisiloxane in a volume ratio of 2:3 to 4:1.

[0019] Preferably, in step 7, the volume ratio of ethanol to hydrogel is 1.2:1 to 1.5:1.

[0020] Preferably, the ultrasonic cleaning time in step 8 is 1 to 2.0 h.

[0021] Preferably, the antistatic agent in step 8 is KKS, model KKS-305; the immersion time in the antistatic agent is 4 to 6 hours.

[0022] Preferably, the oven temperature in step 9 is 140-160°C.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1. The present invention adopts a sol-gel method to prepare SiO2 aerogel, uses fly ash to prepare sodium silicate solution as a precursor for preparing SiO2 aerogel, and adopts a one-step method to complete solvent exchange and surface modification, which not only reduces the production cost of SiO2 aerogel and improves the social and economic value of fly ash and SiO2 aerogel, but also can broaden the application field of fly ash and improve the fly ash processing capacity.

[0025] 2. The composite thermal insulation material of the present invention takes the polymer chain structure as the target, and by extending the linear Si-O-Si structure, the Si-O-Si chain is extended by a mixed precursor method to form more long-chain polymers, and a flexible silicon-based aerogel with high resilience is obtained to increase the flexibility of the polymer chain. The composite thermal insulation material is prepared by mixing and curing glass fiber and SiO2 aerogel by a normal pressure drying method, and the high temperature resistant material glass fiber is used as the reinforcing phase to improve the skeleton strength of the composite thermal insulation material, thereby significantly improving the mechanical properties of the composite thermal insulation material. DETAILED DESCRIPTION

[0026] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the described embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0027] Embodiment 1: A method for preparing a thermal insulation material by extracting SiO2 aerogel composite fibers from fly ash according to the present invention, the preparation method comprising the following steps:

[0028] (1) The fly ash is placed in a constant temperature drying oven for heating and drying at a drying temperature of 150 °C for 30 h to obtain dry fly ash.

[0029] (2) Dry fly ash and sodium carbonate were mixed and ground in a mass ratio of 1:0.5, and then the calcined powder was placed in a muffle furnace for calcination at a calcination temperature of 750 °C for 4 h, and the calcined material was fully ground to obtain a calcined powder with a particle size of 80 μm.

[0030] (3) The calcined powder was added to a 10 wt.% sulfuric acid solution at a solid-liquid ratio of 0.5:1, placed in a magnetic heating stirrer, stirred at an acid leaching temperature of 90 °C and a stirring speed of 500 r / min for 40 min, and then filtered and washed until neutral to obtain silicon slag.

[0031] (4) Adding silicon slag to a 10 wt.% NaOH solution at a solid-liquid ratio of 0.5:1, placing the mixture in a reactor, reacting the mixture at a reaction temperature of 150 °C for 120 min, adding the solid-liquid slurry to a centrifuge for liquid-solid separation, and obtaining a sodium silicate supernatant.

[0032] (5) The sodium silicate supernatant was diluted and hydrolyzed at a silicon-water volume ratio of 1:5, and the diluted and hydrolyzed sodium silicate supernatant was uniformly passed through an ethylene-type cation exchange column for ion exchange, and then 70 wt.% ammonia water was added dropwise to adjust the solution pH to 5.5.

[0033] (6) The pH-adjusted solution was added to an electromagnetic heating stirrer, heated to 40 °C and stirred at a stirring speed of 500 r / min for 30 min. The hydrogel was obtained after the gel was allowed to stand for 24 h.

[0034] (7) Ethanol was added to the hydrogel in a volume ratio of 1.2:1, and then n-heptane solvent and a surface modifier were added in a volume ratio of 1:1. The surface modifier was a mixture of trimethylchlorosilane and hexamethyldisiloxane in a volume ratio of 2:3. The mixture was placed in a water bath at a water bath temperature of 30 °C for 12 h to obtain SiO2 aerogel.

[0035] (8) The glass fiber is immersed in 95% pure anhydrous ethanol and ultrasonically cleaned in an ultrasonic cleaning machine for 1 h to remove oil stains and residual impurities in the fiber. The cleaned fiber is washed and then immersed in an antistatic agent for 4 h. The antistatic agent is KKS-305. The amount of antistatic agent used is appropriate to submerge the fiber.

[0036] (9) SiO2 aerogel and hot melt adhesive powder were dissolved in n-heptane solvent at a mass ratio of 4:1. The antistatic treated fibers were immersed in n-heptane solvent and mixed thoroughly at a mass ratio of fiber to SiO2 aerogel of 1:9. The fibers were then placed in an oven for melting and homogenization at 140 °C for 2 h. The mixture was then cooled to 30 °C and cured for 2 h to obtain a glass fiber reinforced SiO2 aerogel composite insulation material.

[0037] Embodiment 2: A method for preparing a thermal insulation material by extracting SiO2 aerogel composite fibers from fly ash according to the present invention, the preparation method comprising the following steps:

[0038] (1) The fly ash is placed in a constant temperature drying oven for heating and drying at a drying temperature of 165 °C for 27 h to obtain dry fly ash.

[0039] (2) Dry fly ash and sodium carbonate were mixed and ground in a mass ratio of 1:0.75, and then the calcined powder was placed in a muffle furnace for calcination at a calcination temperature of 850 °C for 3 h, and the calcined material was fully ground to obtain a calcined powder with a particle size of 80 μm.

[0040] (3) The calcined powder was added into a 30 wt.% sulfuric acid solution in a solid-liquid ratio of 1:1, placed in a magnetic heating stirrer, stirred for 60 min at an acid leaching temperature of 80°C and a stirring speed of 300 r / min, and then filtered and washed until neutral to obtain silicon slag.

[0041] (4) Adding silicon slag to a NaOH solution with a concentration of 13 wt.% at a solid-liquid ratio of 0.75:1, placing the mixture in a reactor, reacting the mixture at a reaction temperature of 175 °C for 105 min, adding the solid-liquid slurry to a centrifuge for liquid-solid separation, and obtaining a sodium silicate supernatant.

[0042] (5) The sodium silicate supernatant was diluted and hydrolyzed in a ratio of 1:2 in volume of silicon to water, and the diluted and hydrolyzed sodium silicate supernatant was uniformly passed through an ethylene type cation exchange column for ion exchange, and then 60 wt.% ammonia water was added dropwise to adjust the pH value of the solution to 5.5.

[0043] (6) The pH-adjusted solution was added to an electromagnetic heating stirrer, heated to 45 °C and stirred at a stirring speed of 400 r / min for 30 min. The hydrogel was obtained after standing for 30 h to gel.

[0044] (7) Ethanol was added to the hydrogel in a volume ratio of 1.3:1, and then n-heptane solvent and a surface modifier were added in a volume ratio of 1:1. The surface modifier was a mixture of trimethylchlorosilane and hexamethyldisiloxane in a volume ratio of 3:2. The mixture was placed in a water bath at a water bath temperature of 40 °C for 10 h to obtain SiO2 aerogel.

[0045] (8) The glass fiber is immersed in 95% pure anhydrous ethanol and ultrasonically cleaned in an ultrasonic cleaning machine for 1.5 h to remove oil stains and residual impurities in the fiber. The cleaned fiber is washed and then immersed in an antistatic agent for 5 h. The antistatic agent is KKS-305. The amount of antistatic agent used is appropriate to submerge the fiber.

[0046] (9) SiO2 aerogel and hot melt adhesive powder were dissolved in n-heptane solvent at a mass ratio of 4:1. The antistatic treated fibers were immersed in n-heptane solvent and mixed thoroughly at a mass ratio of fiber to SiO2 aerogel of 2:8. The fibers were then placed in an oven for melting and homogenization at 150 °C for 1.5 h, and then cooled to 35 °C and cured for 2.5 h to obtain a glass fiber reinforced SiO2 aerogel composite insulation material.

[0047] Embodiment 3: A method for preparing a thermal insulation material by extracting SiO2 aerogel composite fibers from fly ash according to the present invention, the preparation method comprising the following steps:

[0048] (1) The fly ash is placed in a constant temperature drying oven for heating and drying at a drying temperature of 180 °C for 24 h to obtain dry fly ash.

[0049] (3) Dry fly ash and sodium carbonate were mixed and ground in a mass ratio of 1:1, and then the calcined powder was placed in a muffle furnace for calcination at a calcination temperature of 900 °C for 2 h, and the calcined material was fully ground to obtain a calcined powder with a particle size of 100 μm.

[0050] (3) The calcined powder was added into a sulfuric acid solution with a concentration of 20 wt.% according to a solid-liquid ratio of 0.75:1, and the mixture was placed in a magnetic heating stirrer. After stirring for 50 min at an acid leaching temperature of 85°C and a stirring speed of 400 r / min, the mixture was filtered and washed until neutral to obtain silicon slag.

[0051] (4) Adding silicon slag to a 15 wt.% NaOH solution in a solid-liquid ratio of 1:1, placing the mixture in a reactor, reacting the mixture at a reaction temperature of 200 °C for 90 min, adding the solid-liquid slurry to a centrifuge for liquid-solid separation, and obtaining a sodium silicate supernatant.

[0052] (5) The sodium silicate supernatant was diluted and hydrolyzed at a silicon-water volume ratio of 1:3.5, and the diluted and hydrolyzed sodium silicate supernatant was uniformly passed through an ethylene-type cation exchange column for ion exchange, and then 65 wt.% ammonia water was added dropwise to adjust the solution pH to 5.5.

[0053] (6) The pH-adjusted solution was added to an electromagnetic heating stirrer, heated to 50 °C and stirred at a stirring speed of 300 r / min for 30 min. The hydrogel was obtained after standing for 36 h to gel.

[0054] (7) Ethanol was added to the hydrogel in a volume ratio of 1.5:1, and then n-heptane solvent and a surface modifier were added in a volume ratio of 1:1. The surface modifier was a mixture of trimethylchlorosilane and hexamethyldisiloxane in a volume ratio of 4:1. The mixture was placed in a water bath at a water bath temperature of 50 °C for 8 h to obtain SiO2 aerogel.

[0055] (8) The glass fiber is immersed in 95% pure anhydrous ethanol, and ultrasonically cleaned in an ultrasonic cleaning machine for 2.0 h to remove oil stains and residual impurities in the fiber. The cleaned fiber is washed and then immersed in an antistatic agent for 6 h. The antistatic agent is KKS-305, and the amount of antistatic agent used is appropriate to submerge the fiber.

[0056] (9) SiO2 aerogel and hot melt adhesive powder were dissolved in n-heptane solvent at a mass ratio of 4:1. The antistatic treated fibers were immersed in n-heptane solvent and mixed thoroughly at a mass ratio of fiber to SiO2 aerogel of 3:7. The fibers were then placed in an oven for melting and homogenization at 160 °C for 1 h. The fibers were then cooled to 40 °C and cured for 3 h to obtain a glass fiber reinforced SiO2 aerogel composite insulation material.

[0057] The relevant parameters of the composite thermal insulation material of the present invention are further described by testing and comparative analysis:

[0058] Table 1 shows the analysis results of the chemical composition of fly ash, SiO2%>50%, SiO2+Al2O3+Fe2O3%>80%, CaO%<6%. The soluble substances such as Fe2O3, Al2O3, K2O, Na2O in the fly ash can be removed by acid washing and water washing, thereby enriching SiO2 to obtain silicon slag.

[0059] .

[0060] The silicon content index in fly ash is determined by testing the aluminum dissolution rate in the filtrate after fly ash acid leaching. The higher the aluminum dissolution rate, the purer the silicon content in the solid residue (silicon slag). 3+ The test results are shown in Table 2.

[0061] .

[0062] As shown in Table 2, after repeated experimental verification, when the sintering temperature is 850 ℃, the sulfuric acid concentration is 30 wt.%, and the acid leaching time is 1 h, the aluminum leaching rate can reach more than 93.00%, which can effectively remove aluminum from fly ash and enrich silicon in silicon slag.

[0063] For the sol-gel process of SiO2 aerogel produced by fly ash, the indicators that can reflect the performance of SiO2 aerogel include wet gel density, aerogel density, porosity and linear shrinkage. The test results of the performance indicators of SiO2 aerogel produced in each embodiment are shown in Table 3.

[0064] .

[0065] As shown in Table 3, during the hydrolysis gelation process, the silicon-water ratio and gel pH have a great influence on the performance of SiO2 aerogel. The smaller the silicon-water volume ratio during the hydrolysis process, the greater the density of the obtained SiO2 aerogel sample, the longer the gelation time, and the higher the linear shrinkage rate; in an overly acidic environment, the SiO2 aerogel will have insufficient crosslinking, a larger density, and a smaller porosity; under alkaline conditions, the gelation time becomes shorter, but the aerogel porosity will decrease. Selecting a silicon-water ratio of 1:2 and a gel pH of 5.5 is conducive to improving the quality of SiO2 aerogel.

[0066] The thermal insulation material obtained by adding glass fiber to SiO2 aerogel has significantly improved mechanical properties. However, as a thermal insulation material, its thermal conductivity is the key. The test results of the mechanical properties and thermal conductivity of each embodiment are shown in Table 4.

[0067] .

[0068] It can be seen from Table 4 that according to the comprehensive performance considerations of the composite thermal insulation material, it is necessary to ensure the thermal insulation mechanical strength and take into account the low thermal conductivity of the thermal insulation material. The composite thermal insulation material prepared according to the mass ratio of fiber to SiO2 aerogel of 2:8 has better comprehensive performance.

[0069] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash, characterized in that: The preparation method comprises the following steps: Step 1: placing the fly ash in a constant temperature drying oven for heating and drying to obtain dry fly ash; Step 2: Mix and grind the dry fly ash and sodium carbonate in a mass ratio of 1:0.5-1:1, place in a muffle furnace for calcination, calcine at a calcination temperature of 750-900 °C for 2-4 h, and fully grind the calcined material to obtain a calcined powder; Step 3: adding the calcined powder to a sulfuric acid solution with a concentration of 10-30 wt.% according to a solid-liquid ratio of 0.5:1-1:1, placing it in a magnetic heating stirrer, stirring it at an acid leaching temperature of 80-90°C for 40-60 min, filtering it, washing it to neutrality, and obtaining silicon slag; Step 4: adding silicon slag to a NaOH solution with a concentration of 10-15 wt.% according to a solid-liquid ratio of 0.5:1-1:1, placing the mixture in a reactor, reacting the mixture at a reaction temperature of 150-200 °C for 90-120 min, adding the solid-liquid slurry to a centrifuge for liquid-solid separation, and separating to obtain a sodium silicate supernatant; Step 5: dilute and hydrolyze the sodium silicate supernatant according to a silicon-water volume ratio of 1:2 to 1:5, pass the diluted and hydrolyzed sodium silicate supernatant through an ethylene-type cation exchange column for ion exchange, and then drop ammonia water to adjust the solution pH to 5.0 to 6.0; Step 6: Add the pH-adjusted solution into an electromagnetic heating stirrer, heat and stir evenly, and then let it stand to gel to obtain a hydrogel; Step 7: Add ethanol to the hydrogel, then add n-heptane solvent and surface modifier in a 1:1 volume ratio, place in a water bath, and bathe at a water bath temperature of 30-50 °C for 8-12 h to obtain SiO2 aerogel; Step 8: Immerse the glass fiber in 95% pure anhydrous ethanol, perform ultrasonic cleaning in an ultrasonic cleaning machine to remove oil stains and residual impurities in the fiber, wash the cleaned fiber and then soak it in an antistatic agent; Step 9: Dissolve SiO2 aerogel and hot melt adhesive powder in n-heptane solvent at a mass ratio of 4:1, immerse the antistatic treated fiber in n-heptane solvent at a mass ratio of fiber to SiO2 aerogel of 1:9-3:7, mix thoroughly, and then put into an oven for curing; after cooling, obtain a glass fiber reinforced SiO2 aerogel composite thermal insulation material.

2. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: In step 1, the drying temperature is 150-180°C and the drying time is 24-30 h.

3. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: The particle size of the calcined powder after grinding in step 2 is 50-100 μm.

4. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: In step 5, the concentration of aqueous ammonia is 60-70 wt.%.

5. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: In step 6, the gelation temperature is 40-50°C and the gelation time is 24-36 h.

6. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: In step 7, the surface modifier is a mixture of trimethylchlorosilane and hexamethyldisiloxane in a volume ratio of 2:3 to 4:

1.

7. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: In step 7, the volume ratio of ethanol to hydrogel is 1.2:1 to 1.5:

1.

8. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: The ultrasonic cleaning time in step 8 is 1 to 2.0 h.

9. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: The antistatic agent in step 8 is KKS, model KKS-305; the immersion time in the antistatic agent is 4 to 6 hours.

10. The method for preparing thermal insulation material by extracting SiO2 aerogel composite fiber from fly ash according to claim 1, characterized in that: In step 9, the oven temperature is 140-160°C.

Citation Information

Patent Citations

  • Method for preparing silicon dioxide aerogel by using inorganic mineral as raw material

    CN101224890A

  • Preparation method for modified porous SiO2

    CN104353408A